2015
DOI: 10.5604/20831862.1176302
|View full text |Cite
|
Sign up to set email alerts
|

<strong>OXIDATIVE STRESS AND ANTIOXIDANTS RESPONSES TO PROGRESSIVE RESISTANCE EXERCISE INTENSITY IN TRAINED AND UNTRAINED MALES</strong>

Abstract: The relationship between oxidative stress and some exercise components of resistance exercise (e.g. intensity, exercise volume) has not been clearly defined. Additionally, the oxidative stress markers may respond differently in various conditions. This study aims to determine the effects of progressive intensity of resistance exercise (RE) on oxidative stress and antioxidants in trained and untrained men, and also to investigate the possible threshold intensity required to evoke oxidative stress. RE trained (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Our resistance exercise protocol was suitable to increase oxidative stress as assessed by lipoperoxidation levels in muscle, corroborating previous data about resistance exercise [ 14 17 , 22 ]. A decreased oxidative stress in muscles irradiated with 4J energy demonstrates to be of interest, in which more positive results were noticed for analyses of lipid peroxidation performed immediately after RE bout.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our resistance exercise protocol was suitable to increase oxidative stress as assessed by lipoperoxidation levels in muscle, corroborating previous data about resistance exercise [ 14 17 , 22 ]. A decreased oxidative stress in muscles irradiated with 4J energy demonstrates to be of interest, in which more positive results were noticed for analyses of lipid peroxidation performed immediately after RE bout.…”
Section: Discussionsupporting
confidence: 88%
“…The implication of these findings is a delayed postexercise muscle recovery, hence, impairing the quality of training sessions [ 19 ]. This is a key issue mainly during intense training stages, in which the free radical burst can overcome the antioxidant chemical and enzymatic protection [ 20 ] to maintain redox homeostasis, inducing oxidative damages as observed by Rietjens et al and Cakir-Atabek et al after a single resistance exercise session in men [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, training status can influence OS responses to RT and whey protein together. In young adults, the training status did not influence OS responses to RT alone; however, these results cannot be extrapolated to older people taking protein supplementation.…”
Section: Introductionmentioning
confidence: 64%
“…For example, Cakir-Atabek H et al [197] suggested that RE training has a protective effect against oxidative stress, similar to that induced by CVE training, which is independent of training intensity. Likewise, RE training performed at a very low intensity (30-40% of 1 RM) has been shown to be unable to up-regulate the antioxidant defense system [175], supporting further the notion that high intensity is required for RE-mediated beneficial adaptations to occur. In contrast, findings from the work by Croymans et al [234] revealed that high-intensity RE for 12 weeks, during which both training intensity and volume were progressively increased, did not alter blood lipid profile, total cholesterol levels, HDL, LDL, triglycerides and oxLDL.…”
Section: Regular Resistance Exercise Trainingmentioning
confidence: 65%